Representasi Iklan Shopee Paylater Versi Prilly Latuconsina dalam Menggiring Perilaku Konsumtif Masyarakat Medan 2024 - Azmiral Anwar; Angga Prayuda; Fakhrur Rozi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to examine the influence of Prilly Latuconsina's Shopee PayLater advertising representation on people's consumer behavior, especially in Medan City in 2024. The method used is qualitative research with Charles Sanders Pierce's semiotic analysis approach, which focuses on identifying signs in advertisements and audience interpretation of the messages conveyed. The results of the study show that the Shopee PayLater advertisement featuring Prilly Latuconsina as a brand ambassador has succeeded in attracting the attention of young audiences by conveying messages about the convenience, benefits, and attractive incentives of the service. The discussion shows that well-known public figures are effective in increasing public interest in digital services and influencing consumer behavior. In conclusion, the advertisement has succeeded in strengthening the adoption of Shopee PayLater services and encouraging increased consumption among the community, especially those who are young and open to technological innovation.